Introduction to criminology: theories, methods, and criminal behavior - Hagan, Frank E. (Sage, 2024)
"The Eleventh Edition of bestselling Introduction to Criminology: Theories, Methods, and Criminal Behavior provides students with a comprehensive introduction to the study of criminal behavior with a focus on the core of criminology – theory, method, and criminal behavior. In a clear and accessible manner, authors Frank E. Hagan and Leah E. Daigle present readers with detailed explanations of criminal behavior; examine various forms of criminal activity, such as organized crime, white collar crime, political crime, and environmental crime; the effects on society and policy decisions; and the connection between theory and criminal behavior"--